Asymptomatic Hepatic Leiomyoma in an Immunocompetent Middle-Aged Woman. Issue 11 (24th November 2022) - Nwankwo, Eugene C.; Burton, Samuel J.; Brotherton, Tim; Carpenter, Danielle; Qureshi, Kamran
ABSTRACT: Primary hepatic leiomyomas are rare tumors most commonly in immunosuppressed individuals who are coinfected with Epstein-Barr virus (EBV). From our literature review, there have been 50 published cases, of which 24 were immunocompetent individuals and only 5 were negative for EBV infection. We report a case of primary hepatic leiomyomas in an asymptomatic middle-aged woman without a history of immunosuppression or EBV infection.